2020
DOI: 10.1007/s00421-020-04387-5
|View full text |Cite
|
Sign up to set email alerts
|

Enteric-coated sodium bicarbonate supplementation improves high-intensity cycling performance in trained cyclists

Abstract: Purpose Enteric-coated sodium bicarbonate (NaHCO 3) can attenuate gastrointestinal (GI) symptoms following acute bicarbonate loading, although the subsequent effects on exercise performance have not been investigated. The purpose of this study was to examine the effects of enteric-coated NaHCO 3 supplementation on high-intensity exercise performance and GI symptoms. Methods Eleven trained male cyclists completed three 4 km time trials after consuming; a placebo or 0.3 g•kg-1 body mass NaHCO 3 in enteric-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 48 publications
8
40
0
2
Order By: Relevance
“…Delayed-release or enteric-coated capsules have been reported to delay the occurrence of peak blood alkalosis when compared to gelatine capsules (by approx. 20-24 min [43,44]) in a similar fashion to that seen when comparing the 15 and 60 min ingestion periods in the current investigation (by approx. 20 min).…”
Section: Plos Onesupporting
confidence: 79%
“…Delayed-release or enteric-coated capsules have been reported to delay the occurrence of peak blood alkalosis when compared to gelatine capsules (by approx. 20-24 min [43,44]) in a similar fashion to that seen when comparing the 15 and 60 min ingestion periods in the current investigation (by approx. 20 min).…”
Section: Plos Onesupporting
confidence: 79%
“…McNaughton (17) reported exacerbated GI upset following higher NaHCO 3 doses, while Gough et al (12) observed reduced occurrence of bowel urgency and bloating for 0.2 g.kg −1 compared to 0.3 g.kg −1 BM NaHCO 3 . Reducing the dose is a simple strategy that might remove some of the negative connotations of ingesting this supplement, whilst it is far more cost effective than some of the recent strategies employed to reduce the GI upset following NaHCO 3 ingestion, such as in enteric-coated capsules (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a suggestion that encapsulation may impair or slow down bicarbonate availability through decreased gut transit time (16) changing the optimal pre-exercise ingestion time. Additionally, while the gastro-resistant properties of different capsule forms and their subsequent effects on bicarbonate bioavailability have begun to be elucidated (10,13,17), the effects of the physical properties of capsules, such as their overall size (and therefore surface area), on bicarbonate bioavailability remain unclear.…”
Section: Introductionmentioning
confidence: 99%